Preparation and Characterization of Nanocrystalline Cerium (IV) Oxide and Doped Cerium (IV) Oxide, Ce1-x-yMgxZryO2-? (Journal of Scientific Research, 2015)
Nanocrystalline cerium (IV) oxide is a technologically important material due to its high oxygen storage capacity, oxygen ionic conductivity and thermal stability. In this paper we report preparation of nanocrystalline CeO2 using glycerin nitrate method, where the precursor obtained from the mixture of cerium nitrate and glycerin were calcined at temperatures ranging from 200°C to 800°C in steps of 100°C in a muffle furnace. Attempts were also made to prepare nanocrystalline cerium (IV) oxide doped with both Mg and Zr using the same method. The calcined specimens were characterized using XRD, FTIR and SEM/EDX analyses. The influence of the calcination temperature on the cubic phase formation and its consequent effect on the crystallite size of the prepared CeO2 were studied and interpreted. The crystallite sizes calculated from XRD data using Scherrer formula reveal that the phases are nanocrystals, which was further supported by SEM photograph. The apparent activation energy for crystalline coarsening is found to be very low (26.8 kJmol-1) for this precursor compared to reported data. XRD data and also EDX analysis shows that both Mg and Zr could also be doped in CeO2 upto a certain composition,         Ce1-x-yMgxZryO2-?(x = 0.05, y = 0.05).